HaASR2 from Haloxylon ammodendron confers drought and salt tolerance in plants. (March 2023) - Cao, Yan-Hua; Ren, Wei; Gao, Hui-Juan; Lü, Xin-Pei; Zhao, Qi; Zhang, Hong; Rensing, Christopher; Zhang, Jin-Lin
Abstract: Abscisic acid (ABA), stress, and ripening-induced proteins (ASR), which belong to the ABA/WDS domain superfamily, are involved in the plant response to abiotic stresses. Haloxylon ammodendron is a succulent xerohalophyte species that exhibits strong resistance to abiotic stress. In this study, we isolated HaASR2 from H. ammodendron and demonstrated its detailed molecular function for drought and salt stress tolerance. HaASR2 interacted with the HaNHX1 protein, and its expression was significantly up-regulated under osmotic stress. Overexpression of HaASR2 improved drought and salt tolerance by enhancing water use efficiency and photosynthetic capacity in Arabidopsis thaliana . Overexpression of HaASR2 maintained the homeostasis of reactive oxygen species (ROS) and decreased sensitivity to exogenous ABA and endogenous ABA levels by down-regulating ABA biosynthesis genes under drought stress. Furthermore, a transcriptomic comparison between wild-type and HaASR2 transgenic Arabidopsis plants indicated that HaASR2 significantly induced the expression of 896 genes in roots and 406 genes in shoots under osmotic stress. Gene ontology (GO) enrichment analysis showed that those DEGs were mainly involved in ROS scavenging, metal ion homeostasis, response to hormone stimulus, etc. The results demonstrated that HaASR2 from the desert shrub, H. ammodendron, plays a critical role in plant adaptation to drought and salt stress and could be a promising gene for the genetic improvement of crop abiotic stress tolerance. Highlights: HaASR2 was isolated from a desert shrub, Haloxylon ammodendron, and its molecular function was analyzed in Arabidopsis. Overexpression of HaASR2 enhanced drought and salt tolerance through improving water use efficiency and photosynthetic capacity in Arabidopsis. Overexpression of HaASR2 maintained ROS homeostasis and decreased the sensitivity of plants to exogenous and endogenous ABA.